DEVELOPMENT AND VALIDATION OF DISSOLUTION METHOD FOR LINAGLIPTIN TABLETS - PANSARE, MEGHANA; DAMLE, MRINALINI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Linagliptin is used to treat type-2 diabetes. It is available singly as 5 mg tablet. Since there is no official dissolution method in Indian pharmacopeia, there is a need to develop a method for testing dissolution of linagliptin immediate release tablet. Methods: For establishing dissolution method, various media, volume of media, and speed of rotation were tried. Quantification of dissolution samples was carried out using HPTLC and UV method. TLC plate pre-coated with silica gel 60 F254 was used as stationary phase and mobile phase employed for the development of TLC plates was methanol: toluene in a ratio of 7:3 v/v. The mobile phase was allowed to travel a distance of 70 mm and saturation time set was 20 min. Detection wavelength set was 294 nm. Results: The most suitable condition for dissolution of linagliptin tablet was found to be dissolution apparatus type II (paddle) using 900 ml 0.1 N HCl as medium at speed of 75 rpm. The optimized chromatographic condition resulted in compact band at Rf value of 0.76±0.02. Conclusion: Both the chromatographic and spectroscopic methods which were used for quantification were found to be linear with r2 value of 0.9929 and 0.9918, respectively, accurate, precise, and robust.